A Companion to global historical thought - Murthy, Viren; Sartori, Andrew (Wiley-Blackwell, 2014)
A Companion to Global Historical Thought provides an in-depth overview of the development of historical thinking from the earliest times to the present, across the world, directly addressing the issues of historical thought in a globalized context. Provides an overview of the development of historical thinking from the earliest times to the present, across the world, through essays written by a team of leading international scholarsComplements the Companion to Western Historical Thought, placing non-Western perspectives on historiography at the center of the discussionExplores the different his.
Includes bibliographical references and index.
Print version record.
Keywords: History -- Philosophy; History, Ancient -- Historiography; History, Modern -- Historiography; Electronic books